Effect of whole-body vibration stimulation on plasma soluble TNF receptors in elderly with sarcopenia: a randomized controlled trial - Almeida, H. C.; Lage, V. K. S.; Taiar, R.; Santos, J. M.; Paula, F. A. de; Rapin, A.; Sá-Caputo, D. C.; Bernardo-Filho, M.; Lacerda, A. C. R.; Mendonça, V. A. (Brazilian Journal of Medical and Biological Research, 2024)
Abstract Sarcopenia is a pathology resulting from a progressive and severe loss of muscle mass, strength, and function in the course of aging, which has deleterious consequences on quality of life. Among the most widespread studies on the issue are those focused on the effect of different types of physical exercise on patients with sarcopenia. This randomized controlled study aimed to compare the effects of a whole-body vibration exercise (WBV) session on the inflammatory parameters of non-sarcopenic (NSG, n=22) and sarcopenic elderly (SG, n=22). NSG and SG participants were randomly divided into two protocols: intervention (squat with WBV) and control (squat without WBV). After a one-week washout period, participants switched protocols, so that everyone performed both protocols. Body composition was assessed by dual-energy radiological absorptiometry (DXA) and function through the six-minute walk test (6MWD) and Short Physical Performance Battery (SPPB). Plasma soluble tumor necrosis factor receptors (sTNFR) were determined by enzyme-linked immunosorbent assay (ELISA) and measured before and immediately after each protocol. After exercise with WBV, there was an increase in sTNFR2 levels in the NSG (P<0.01; d=-0.69 (-1.30; -0.08) and SG (P<0.01, d=-0.95 (-1.57; -0.32) groups. In conclusion, an acute session of WBV influenced sTNFr2 levels, with sarcopenic individuals showing a greater effect. This suggested that WBV had a more pronounced impact on sTNFr2 in those with loss of muscle strength and/or physical performance. Additionally, WBV is gaining recognition as an efficient strategy for those with persistent health issues.
Keywords: Elderly; Inflammation; Sarcopenia; TNFR; Whole-body vibration